Electric power construction vehicle emergency traction mode control method - WANG WENFENG; HUANG HAI; LIAO HONGTAO; LIU HUAN; GUO WANLU; LIU SHIJIE; ZHANG SHUXUN (2017)
The invention discloses an electric power construction vehicle emergency traction mode control method, which comprises the following steps that when a network control system generates a fault, an emergency traction conversion switch receives an emergency traction system starting signal input by a driver to provide a power supply for an emergency traction device; the emergency traction system starting signal is sent to the emergency traction device; the emergency traction device is started; the emergency traction device sends the emergency traction system starting signal to a traction inverter; the traction inverter configures the emergency traction system according to the emergency traction system starting signal; the emergency traction system enters the emergency traction mode. The normal traction function of a construction vehicle in the emergency mode is realized by the method. 本发明公开了种电力工程车紧急牵引模式控制方法，该方法包括：当网络控制系统出现故障时，紧急牵引转换开关接收司机输入的紧急牵引系统启动信号，为紧急牵引装置提供电源，并将所述紧急牵引系统启动信号发送至所述紧急牵引装置，启动所述紧急牵引装置；所述紧急牵引装置将所述紧急